(untitled) (Revista de Crítica Literaria Latinoamericana, 2012)
This article analyzes the poetry of Juan Luis Martínez and Raúl Zurita in the context of neo-avant-garde Spanish American poetry. One of the most salient features of this poetry is its profound reflection about language and the materiality of writing. I analyze the poems "La realidad I" and "La realidad II" by Juan Luis Martínez, and "Areas verdes" by Raúl Zurita. This early texts interact with the wide web of Spanish American writing, creating a dialogue between reality and writing, art and representation.